2018
DOI: 10.1371/journal.pone.0194208
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of the SAMe-TT2R2 score: A systematic review and simulation meta-analysis

Abstract: BackgroundVitamin K antagonist (VKA) therapy is safer and more effective when patients have a high time within the therapeutic range and low international normalised ratio variability. The SAMe-TT2R2 score aims to identify those at risk for poor VKA control.ObjectivesTo evaluate the predictive value and clinical usefulness of the SAMe-TT2R2 score to identify those at risk for poor VKA control.MethodsWe performed a systematic review in MEDLINE and Embase for original research papers assessing the SAMe-TT2R2’s r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…Regarding the SAMe‐TT 2 R 2 score, in this study, we found that higher scores were related to switching, consistent with its original objective that was to predict which patients do well with VKAs, and several studies have demonstrated that it was able to predict poor INR (ie poor TTR), thus, aiding decision‐making 22,24‐26 . However, the predictive ability of the SAMe‐TT 2 R 2 score for switching in the present study was limited, which has also been observed in the past 22,27 . Nevertheless, we found higher switching to DOACs in the nurse‐led clinic.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Regarding the SAMe‐TT 2 R 2 score, in this study, we found that higher scores were related to switching, consistent with its original objective that was to predict which patients do well with VKAs, and several studies have demonstrated that it was able to predict poor INR (ie poor TTR), thus, aiding decision‐making 22,24‐26 . However, the predictive ability of the SAMe‐TT 2 R 2 score for switching in the present study was limited, which has also been observed in the past 22,27 . Nevertheless, we found higher switching to DOACs in the nurse‐led clinic.…”
Section: Discussionsupporting
confidence: 82%
“…22,[24][25][26] However, the TA B L E 1 Baseline characteristics predictive ability of the SAMe-TT 2 R 2 score for switching in the present study was limited, which has also been observed in the past. 22,27 Nevertheless, we found higher switching to DOACs in the nurse-led clinic. This is of importance since DOACs have shown a clear benefit over warfarin in terms of safety and efficacy.…”
Section: Discussionmentioning
confidence: 63%
“…(25) A recent systematic review on 16 studies summarised that although the SAMe-TT2R2 score can predict low TTR, the effect is too small to be clinically useful. (26) In our study, 67.4% of the patients had TTR < 65%, which is considered suboptimal. Even at a SAMe-TT2R2 score of 2, 64.1% of the patients had a TTR of < 65%, indicating that the discriminative power of the score is limited; this correlated with the low C-statistic.…”
mentioning
confidence: 56%
“…This can be problematic because even significant differences between groups allow for considerable overlap (eg, in our data set, analysis of variance for TTR by strata resulted in a P value <.01 for all time points in Figure 2). Furthermore, these tools do not provide a probability for a certain TTR, making them less clinically useful 19 …”
Section: Discussionmentioning
confidence: 99%